El control interno contable de propiedad, planta y equipo y su aporte a la razonabilidad de los estados financieros - Loza Quezada, Ana María (2015)
This work aims to propose qualifications to the company Orominex SA manual internal accounting control for property, plant and equipment. Through the COSO II tool and the application of the elements is determined that the control of the group is not efficient, the risks are identified, there are no established duties, the accounting records are unreliable, this results in the financial statements are unreasonable, it is recommended to the company Orominex SA implementing a manual of internal accounting control to property, plant and equipment, train staff, communication between management and employees, incorporate a module to the accounting system to control property, plant and through computer technology, the implementation of these recommendations will help to meet the management objectives of the company.